Temperature damage regularity of granite based on micro-inhomogeneity - Du, Guangsheng; Chen, Shijiang; Chen, Xiaoyi; Jiang, Zheng (Frontiers in Earth Science, 2022)
During the construction of an enhanced geothermal system (EGS), a large-scale underground reservoir needs to be constructed. Under the impact of temperature, the variation of mechanical properties of granite and the development of cracks have a great influence on the effect of this procedure. In order to study the concerning micro-influencing factors, referring to the mechanism of rock damage and destruction, the coupling model of GBM equivalent crystalline model and Thermal temperature field is constructed through the quantitative description of crystalline rock inhomogeneity parameter H and the discrete element software. At different temperatures, damage and crack development laws of different inhomogeneity coefficients were studied. The results show that (1) both the coefficient of inhomogeneity and the rise of temperature of granite lead to the degradation of its mechanical properties; (2) With the increase of inhomogeneity coefficient, the damage value D increases continuously at a certain temperature, and this phenomenon becomes more obvious when the temperature is higher than 400 ℃. (3)it is not easy to form intra-crystal shear cracks due to temperature, and the increase in inhomogeneity leads to the development of intra-crystal cracks in the total number of micro-cracks. (4) The damage effect caused by temperature is affected by the micro-inhomogeneity of granite. The combination of crystal denaturation and inhomogeneous stress concentration results in a faster deterioration of rock strength at high temperatures.